2006
DOI: 10.1007/bf02974279
|View full text |Cite
|
Sign up to set email alerts
|

An antioxidative and antiinflammatory agent for potential treatment of osteoarthritis fromEcklonia cava

Abstract: Osteoarthritis is thought to be induced by the ageing-related loss of homeostatic balance between degeneration and repair mechanism around cartilage tissue in which inflammatory mediators such as reactive oxygen species, cytokines and prostaglandins are prone to over-production under undesirable physiological conditions. Phlorotannins are unique polyphenolic compounds bearing dibenzo-1,4-dioxin skeleton which are not found in terrestrial plants but found only in some brown algal species such as Ecklonia and Ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
93
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(95 citation statements)
references
References 26 publications
1
93
0
1
Order By: Relevance
“…32 Furthermore, phlorotannin-rich extracts have shown significant antioxidant radical scavenging activity, showing strong OA therapeutic benefits through in vitro experiments. 33 The purpose of the present study was to compare the effectiveness of 2 concentrations (10% and 20%) of a unique blend of comfrey root extract (S officinale L.), TA, and eucalyptus to a reference cream containing eucalyptus only on primary knee OA pain, stiffness, and physical functioning. To our knowledge, the combination of comfrey and TA in the treatment of OA is unique and has yet to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…32 Furthermore, phlorotannin-rich extracts have shown significant antioxidant radical scavenging activity, showing strong OA therapeutic benefits through in vitro experiments. 33 The purpose of the present study was to compare the effectiveness of 2 concentrations (10% and 20%) of a unique blend of comfrey root extract (S officinale L.), TA, and eucalyptus to a reference cream containing eucalyptus only on primary knee OA pain, stiffness, and physical functioning. To our knowledge, the combination of comfrey and TA in the treatment of OA is unique and has yet to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Ecklonia cava, brown algae (Laminariaceae) abundant around Jeju Island in Korea, contains phlorotannin components with known biological activities [6,7]. Phlorotannin has anti-inflammatory effects [6] and protects cells from oxidative stress by scavenging intracellular ROS [7].…”
Section: Introductionmentioning
confidence: 99%
“…Phlorotannin has anti-inflammatory effects [6] and protects cells from oxidative stress by scavenging intracellular ROS [7]. Phlorotannin, which is a phloroglucinol polymer found in marine algal polyphenols, has been identified in various Ecklonia species [8].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, several species of seaweeds are used in cosmetics, food, and pharmaceuticals. Many studies have shown that seaweeds have diverse bioactivities such as antioxidant, anticoagulant, anti-inflammation, antibacterial, and anticancer activities (Heo et al 2003, Shin et al 2006, Kim et al 2007, Erbert et al 2012, Ko et al 2012. In particular, Ecklonia cava is a common edible brown algae that is plentiful in Jeju Island of Republic of Korea.…”
mentioning
confidence: 99%